Renewable energy resource of Sri Lanka! A review - Sayanthan, S.; Kannan, N. (International Journal of Environmental & Agriculture Research (IJOEAR), 2017)
Energy and related sectors play a key role in the developmental profile of Sri Lanka. Energy demand is going up and up with time due to population growth and industrial revolutions. In order to meet such growing needs probably we are relying on fossil fuel in a large fraction, which is leading to many negative environmental impacts. Hence the government decided to take off many long term as well as short term planes to promote renewable energy sector in Sri Lanka as it gives minimum impact to environment and its quality than the fossil fuel. This paper gives basic information about renewable energy resources of Sri Lanka and their development &future perspectives.
Keywords: Renewable Energy; Fossil fuel; Sri Lanka; Environment